Potential Pulse ALD for Room Temperature Fabrication of Stoichiometric CdTe Nanofilms. Issue 5 (27th February 2019) - Zhang, Xiaoyue; Shen, Sheng; Howell, Paulie; Cheng, Wei; Mubeen, Syed; Stickney, John
Abstract : Deposition of thin film compound semiconductors with good control over stoichiometry, crystallinity and thickness is essential for a range of diverse applications such as solar cells, photocatalysis, thermoelectrics, photodetectors, etc. In this work, nanometer-thick cadmium telluride (CdTe) films with exceptional control over its stoichiometry were electrodeposited onto Au substrates using a novel potential pulse atomic layer deposition (PP-ALD) process. The films were electrodeposited from an acidic aqueous solution of CdSO4 and TeO2 at room temperature using a flow cell electrodeposition set-up. Deposition potential and effect of solution flow were first investigated to optimize the codeposition process. Potential pulses were then subsequently introduced to achieve atomic layer deposition of CdTe. X-ray diffraction (XRD), Scanning electron microscope (SEM), Electron probe microanalysis (EPMA), Energy Dispersive X-Ray Analyzer (EDX) were used to characterize resulting CdTe films. XRD studies of the films showed the evolution of a much sharper peak corresponding to CdTe cubic (111) than is customarily observed for CdTe thin films grown at room temperature. The optimized PP-ALD method was also used to deposit CdTe on Au nanowire-array electrodes. Initial results show high-quality CdTe deposits conformally coated on Au nanowire arrays, which could open pathways for ultrathin light absorber solar energy conversion devices.